2019
DOI: 10.1097/pec.0000000000001750
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Clinical Findings Based on the Duration of Symptoms and Age of Children With Ileocolic Intussusception

Abstract: Objectives:The objective of this study was to determine whether the rates of abdominal pain or irritability, vomiting, and hematochezia differ depending on the duration of symptoms and age of the children with ileocolic intussusception. Methods:We retrospectively investigated the charts of ileocolic intussusception children between January 2008 and December 2017 at a rural general hospital in Japan. Children were separated into 2 groups: the early visiting group, including children examined within 6 hours afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 21 publications
2
7
1
4
Order By: Relevance
“…The second most common symptom was vomiting (46.1%, n = 247). Vomiting was significantly more common in younger children ( P < 0.001), similar to previous studies ( 3 , 15 ). Vomiting is caused by a vagal reflex and ileus condition.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The second most common symptom was vomiting (46.1%, n = 247). Vomiting was significantly more common in younger children ( P < 0.001), similar to previous studies ( 3 , 15 ). Vomiting is caused by a vagal reflex and ileus condition.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, post-enema bloody stool was also more common in younger children ( P < 0.001), and children older than 2 years tended to have a normal stool (no blood in the stool) even after glycerin enema (77.1%). Bloody stool may occur as a result of the compression of the mesenteric vessels, mucosal edema, hemorrhage, and ischemia of the bowel, and may not be detected in early cases ( 15 , 19 ). Bloody stool was significantly more common in the late than in the early group ( P = 0.023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we could not show any relationship between symptom duration and bloody stools in our study, in contrast to most other studies. 9,25 Some authors have reported that symptom duration and door-to-diagnosis time are longer in patients aged older than 2 years. 9 We found no relationship between patient age and symptom duration.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Park et al 9 reported that abdominal pain was less frequent in patients aged younger than 2 years. Aoki et al 25 noted that in infants younger than 18 months, abdominal pain or irritability were less frequent and vomiting and bloody stool were more frequent.…”
Section: Discussionmentioning
confidence: 99%